Association of thoracic aortic calcium with incident cardiovascular disease and all-cause mortality across the spectrum of coronary artery calcium burden - Alexander C. Razavi; Omar Dzaye; Miguel Cainzos-Achirica; Zeina Dardari; Marly Van Assen; Arshed A. Quyyumi; Khurram Nasir; J. Jeffrey Carr; Matthew J. Budoff; Roger S. Blumenthal; Paolo Raggi; Carlo N. De Cecco; et al. (American Journal of Preventive Cardiology)
Background: Calcification of the ascending and/or descending thoracic aorta is easily measured via non-contrast cardiac computed tomography (CT), commonly performed for quantification of coronary artery calcium (CAC). We assessed whether thoracic aortic calcium (TAC) further improves long-term cardiovascular disease (CVD) risk stratification beyond CAC alone. Methods: Cardiac CT was performed among 6,783 asymptomatic Multi-Ethnic Study of Atherosclerosis participants at baseline. Cox proportional hazards regression assessed the association of TAC with incident CVD and all-cause mortality over a median follow-up of 17.7 years, adjusting for CVD risk factors and CAC. Results: The mean age was 62.1 years old, 53% were female, and 28% had TAC. Over a median follow-up of 17.7 years, 48% of participants with TAC ≥500 experienced CVD and 72% died. Compared to TAC=0, TAC ≥500 was significantly associated with an increased risk of CVD (HR=1.28, 95% CI: 1.06-1.54) and all-cause mortality (HR=1.44, 95% CI: 1.25–1.65), with the strongest association among persons with CAC=0 (CVD HR=1.79, 95% CI: 1.04–3.07; all-cause mortality HR=1.82, 95% CI: 1.29–2.56). The addition of TAC to traditional risk factors and CAC did not improve CVD discrimination (ΔC-statistic=+0.002, p=0.12), but incrementally improved prediction of all-cause mortality (CVD: ΔC-statistic=+0.002, p=0.02). Conclusions: Participants with TAC ≥500 had a high long-term risk for CVD and all-cause mortality. TAC primarily improved risk stratification among persons with CAC=0.